Students perception and acceptance of problem-based learning (PBL) in a hybrid traditional-PBL curriculum - Sim, Si Mui; Lian, Lay Hoong; Kanthimathi, M.S.; Thong, Meow Keong; Tan, Nget Hong (2011)
Even though there are several variants in its implementation, problem-based learning (PBL) is essentially a form of student-centred learning that involves enquiry-based discussion triggered by a problem and facilitated by a tutor in small groups. In a hybrid traditional-PBL curriculum where PBL runs parallel with conventional didactic teaching, there is always a concern that such curricular arrangement may produce undesirable learning behaviour. Therefore, this paper evaluated the students' perception and acceptance of PBL in such a learning environment. PBL was introduced in a gradual manner into the first three years of a revised undergraduate medical curriculum at the University of Malaya (UM) in 1999/2000. Self-administered questionnaires were distributed to students of Phases I, II (first two preclinical years) and IIIA (first of the three clinical years) after completing their respective final examination papers. The study compared the responses of at least nine cohorts of students (2001 to 2009) on questions related to PBL. Students were asked to respond to each question based on their own experience using a 5-point Likert scale. Across the board, progressively over the years, students from all the phases reported an improvement in their critical thinking, integration of knowledge, appreciation of understanding rather than merely memorising facts, communication skills, and braveness to counter-propose opinions. The effects were more obvious with Phase I students compared with students from the other two phases. Written comments from the students also showed a shift from resistance and outright call for the abolishment of PBL tutorials, to positive call to increase PBL tutorials.